Training on Making Bokashi Fertilizer in Dosan Village, Pusako District, Siak Regency: Pelatihan Pembuatan Pupuk Bokashi di Desa Dosan Kecamatan Pusako Kabupaten Siak - Fathurrahman; Satriana Dewi, Ilma; Salman, Salmita; Kustiawan, Nursamsul; Heriyanto (Universitas Lancang Kuning, 2024)
Community service activities have been carried out in Dosan Village in Dosan Village, Pusako District, Siak Regency, where most of the people are farmers. Based on the results of an initial survey of several farmers and village officials who wanted to know information about making bokashi, it can be concluded that the people of Dosan Village deserve training on bokashi making techniques. The training was carried out with the aim of increasing the knowledge and skills of village communities in processing organic waste from household and agricultural waste. The service activities will be carried out for 6 months, starting from the preparation of the service team to partner locations to monitoring and evaluation and publication as a form of output from this service activity. Service activities are carried out using lecture and demonstration methods. The results of the service activities showed that there was an increase in partner participants' knowledge regarding bokashi fertilizer before and after the activity with percentage of 76 to 86%. The results of the paired t-test also show that there is a significant difference in the increase in farmers' knowledge before and after community service activities.